PERAN PELATIHAN MODERASI BERAGAMA TERHADAP PERSEPSI PESERTA PELATIHAN TENTANG PANDANGAN, SIKAP, PRAKTIK MODERASI BERAGAMA - Dermawati, Dermawati (Balai Diklat Keagamaan Jakarta, 2024)
Abstract This research aims to see the role of religious moderation training on participants' perceptions in the form of views, attitudes, and religious practices regarding the concept of religious moderation, national insight, religious insight, and implementation of religious moderation after attending training to strengthen religious moderation in East Jakarta. This research method combines data collection techniques using qualitative and quantitative data from pre-test and post-test results. The test instrument consists of questions with open answers and a Likert scale. The two data sets were compared and analyzed descriptively and using a t-test. The results of this research show that the introduction to the concept of religious moderation after training in the form of an understanding of religious moderation, indicators of religious moderation, and the values of religious moderation are broadly not fully understood. For the concept of insight, which includes Pancasila, the training participants stated that it was final, but there were differences of opinion between political movements that were considered to be able to change the basis of the country while regarding the concept of religious insight and the implementation of religious moderation before and after the training the results were almost the same on average. This research concludes that the role of religious moderation training is insignificant in participants' perceptions of the views, attitudes, and practices of religious moderation and the need to increase participants' understanding of the concept of religious moderation. Abstrak Penelitian ini bertujuan melihat peran pelatihan moderasi beragama terhadap persepsi peserta berupa pandangan, sikap, praktik beragama tentang konsep moderasi beragama, wawasan kebangsaan, wawasan keagamaan dan implementasi moderasi beragama setelah mengikuti pelatihan penggerak penguatan moderasi beragama Jakarta Timur. Metode penelitian ini adalah penelitian campuran (mixed methods) dengan teknik pengumpulan data menggunakan data kualitatif dan kuantitatif yang didapatkan dari hasil pre-test dan post-test . Instrumen tes terdiri dari pertanyaan dengan jawaban terbuka dan skala likert. Kedua data dibandingkan serta dianalisis secara deskriptif dan uji-t. Hasil penelitian ini menunjukkan pengenalan terhadap konsep moderasi beragama setelah pelatihan berupa pengertian moderasi beragama, indikator moderasi beragama, serta nilai-nilai moderasi beragama sebagian besar belum memahami secara utuh. Untuk konsep wawasan kebangsaan mencakup Pancasila, peserta pelatihan menyatakan sudah final tapi ada perbedaan pendapat antara gerakan politik yang dianggap dapat mengubah dasar negara, sedangkan tentang konsep wawasan keagamaan dan implementasi moderasi beragama sebelum dan sesudah pelatihan hasilnya rata-rata hampir sama. Kesimpulan dari penelitian ini adalah bahwa peran pelatihan moderasi beragama tidak signifikan terhadap persepsi peserta terhadap pandangan, sikap dan praktik moderasi beragama serta perlu peningkatan tentang pemahaman peserta terhadap konsep moderasi beragama.